PRE-ANAESTHETIC ASSESSMENT OF INTRACRANIAL PRESSURE USING OPTIC NERVE SHEATH DIAMETER IN PATIENTS SCHEDULED FOR ELECTIVE TUMOUR CRANIOTOMY - Shafiq, Faraz; Ali, Muahmmad Asghar; Khan, Fauzia Anis (Journal of Ayub Medical College Abbottabad, 2018)
Background: The objective of study was to determine the pre-anaesthetic status of intracranial pressure (ICP), using ultrasonographic measurement of optic nerve sheath diameter (ONSD) in-patient scheduled for elective tumour craniotomy. The secondary objective was to compare the diagnostic accuracy of ONSD guided rise in ICP with clinical and radiographic parameters. This is prospective observational study, conducted at single neurosurgical theatre of The Aga Khan University over a period of one year. Methods: After getting ethical approval and informed consent patient fulfilling inclusion criteria and planned for elective tumour craniotomy were enrolled in study. The clinical and radiographic signs predicting the status of ICP were recorded. The ultrasonographic measurement of ONSD was done using liner array probe. Value more than 5 mm was considered as abnormal. Results: Total 26 cases were enrolled. Seventy percent patients showed rise in ICP based on clinical parameters, while 65% diagnosed to have raised ICP on the basis of radiographic findings. The ultrasonographic measurement of ONSD predicted this rise in 61% of cases. The diagnostic accuracy of ONSD in detecting raised ICP in comparison to clinical and radiographic evidence was 87.5% respectively. Conclusion: The ultrasonographic-guided ONSD was used successfully for predicting the status of ICP in pre-induction phase of anaesthesia. It also showed good correlation in diagnosing rise in ICP as compared to clinical and radiographic parameters, which indicates that test can be used reliably in preoperative period for patients planned for tumour craniotomy. Keywords: Craniotomy; intracranial pressure; optic nerve